Yolk sac tumor and dysgerminoma in the left gonad following gonadoblastoma in the right gonad in a 46,XY DSD with a novel SRY missense mutation: a case report - Chengxiu Xie; Jian Cai; Nan Li; Ping Hua; Zexuan Yang; Xia Yu; Dongmei Tang; Yu Hu; Qingsong Liu (BMC, 2023)
Abstract Background Approximately 10-15% of 46,XY disorders of sex development (DSDs) have an SRY mutation residing in the high mobility group (HMG) domain. Here, we present a case of 46,XY DSD caused by a novel missense mutation in the HMG region of SRY rapidly progressing to germ cell tumors (GCTs). Case presentation An adolescent female (15 years old) exhibiting primary amenorrhea was later diagnosed as a 46,XY female with bilateral gonadal dysplasia on the basis of peripheral lymphocyte karyotype 46,XY and a novel missense mutation in SRY (c.281 T > G, p.L94R). The novel missense mutation (c.281 T > G, p.L94R) and its adjacent region were conserved. Protein structure analysis showed that the mutant site was located in the middle of the HMG domain, and the mutant protein had a diminished ability to bind to DNA. Imaging examination revealed an adolescent female with a naive uterus. Laparoscopy and initial pathological examination revealed left gonadal dysplasia and right gonadal dysplasia with gonadoblastoma (GB). Right gonadectomy by laparoscopy was performed upon consent from the patient's parents. Less than 1 year postoperatively, the left gonadal gland deteriorated as observed by the findings of a mass in the left adnexal region by pelvic MRI and serum AFP > 1000 ng/ml by serological tests, and then total hysterectomy and adnexal and left gonadectomy by laparoscopy were performed. The GCT stage was classified as stage Ic according to FIGO. At this time, pathologic examination showed that the left gonad had progressed to yolk sac tumor and dysgerminoma. The patient underwent chemotherapy post-operatively but developed type III myelosuppression and tumor recurrence several months later. Conclusions The patient initially presented with right gonadoblastoma but chose only right gonadectomy by laparoscopy to preserve the female sex characteristics, which resulted in rapid deterioration of the left gonad and poor treatment outcomes. This case demonstrates the importance of early genetic diagnosis and treatment of 46,XY female DSD.